Differences in information acquisition and justice sensitivity predict adoption of apps affecting own and others' privacy - Rabia I. Kodapanakkal; Christoph Kogler; Mark J. Brandt; Ilja van Beest (Acta Psychologica)
Many apps (e.g., social media, online streaming) include a social component where individual privacy decisions go beyond individual contexts and affect other people. We investigated people's willingness to adopt four apps and assessed the attentional processes underlying how people make tradeoffs when their own privacy and/or others' privacy is violated in a within-subjects design (NStudy1 = 304; NStudy2 = 355). We also assessed individual differences in the willingness to adopt apps in terms of other-oriented traits (e.g., empathic concern, justice sensitivity etc.). The main findings show that (1) when own privacy was protected and others' privacy was not protected, people were more willing to adopt apps (compared to when others' privacy was protected and own privacy not protected). (2) Individual differences in information acquisition predicted the decision to adopt apps. More attention to others' privacy information was associated with lower willingness to adopt apps when others' privacy was not protected. (3) Higher sensitivity to justice and self-transcendence values were associated with lower adoption of the apps when self or other-privacy violations were present. Our results suggest that people differ in how much they care about whether their privacy decisions might affect others negatively. Accordingly, they differ in their attention to privacy information especially in situations where own and others' privacy is in conflict. People's justice concerns extend to concern for both self and other-privacy violations. These findings imply that although people may care about privacy, individual differences are important to understand why people care about own and others' privacy differently.